Effect of heat stress or lipopolysaccharide (E-coli) injection on HSP70 levels in the liver and brain of adrenalectomized rats - Nishizawa, M.; Giviziez, PEN; Ferro, J. A.; Ferro, MIT; Macari, Marcos [UNESP] (Elsevier B.V., 1999)
Hsp70 content (ng Hsp70 mu g total protein(-1)) in the liver and brain of control and adrenalectomized male rats was investigated by Western Blotting after heat stress (40 degrees C) or endotoxin-induced fever (E. coli lipopolysaccharide injection). The increase in rectal temperature was higher after heat stress than after LPS injection, Heat stress affected Hsp70 content of the liver, but not of the brain; however adrenalectomy did not influence any parameter. These results suggest that, under these circumstances, there is no relationship between the hypothalamic-pituitary-adrenal axis and Hsp70 synthesis in liver and brain. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: adrenalectomy; heat stress; Hsp70; lipopolysaccharide-induced fever